New insight of itch mediators and proinflammatory cytokines in epidermolysis bullosa. Issue 3 (7th February 2022) - Nguyen, Hong Ha; Shinkuma, Satoru; Hayashi, Ryota; Katsumi, Tatsuya; Nishiguchi, Tomoki; Natsuga, Ken; Fujita, Yasuyuki; Abe, Riichiro
Abstract: Objectives: Epidermolysis bullosa (EB) is a hereditary disorder characterized by mechanical stress‐induced blistering. The presence of extracutaneous complications such as cardiomyopathy and renal disease observed in severe EB subtypes and the fact that pruritus is a common symptom across all EB subtypes indicate that EB is not only a skin fragility disease but also a systemic inflammatory disorder. Our study aims to elucidate the basis of the systemic inflammation seen in EB patients. Methods: We analyzed serum samples of 20 EB patients by Luminex bead‐based cytokine assays and enzyme‐linked immunosorbent assays. Results: The serum levels of sIL‐2R, IL‐6, HGF, M‐CSF, SCGF‐β, IL‐8, IL‐16, IFN‐γ, MIF, MIP‐1α, and thymic stromal lymphopoietin (TSLP) ( p  < .01, p  < .01, p  < .01, p  < .01, p  < .01, p  < .05, p  < .05, p  < .05, p  < .05, p  < .05, and p  = .01, respectively) were found to be significantly elevated in EB patients, whereas TNF‐β ( p  < .01) was decreased. Th2 cytokines including IL‐4, IL‐5, and IL‐13 were not elevated in EB patients. In contrast, TSLP was significantly increased, and IL‐31 and oncostatin M were not statistically significant but tended to be higher in the patients than in healthy controls. Among proinflammatory cytokines such as IL‐1β, IL‐6, and TNF‐α, IL‐6 was elevated in EB patients. Conclusions: The imbalance of several itch mediators and proinflammatory cytokines was identified. Biologics targeting the cytokines found to be elevated in the sera of patients is considered as a beneficial treatment option for EB. Abstract : The imbalance of several itch mediators (TSLP, IL‐31, and oncostatin M) and proinflammatory cytokine (IL‐6) was identified in patients with epidermolysis bullosa.